Treatment of alopecia areata based on the theory of Traditional Chinese Medicine internal treatment combined with external treatment (基于络病理论中医内外治结合治疗斑秃应用研究) - WANG Yunong (王羽侬); LI Yue (李悦); ZHANG Panpan (张攀攀) (中西医结合护理)
Alopecia areata (AA) is a common autoimmune hair loss disease. Under the guidance of Traditional Chinese medicine (TCM) syndrome differentiation theory and combined with collateral disease theory, this article summarized the etiology, pathogenesis, clinical characteristics, treatment principles, treatment methods, and prescriptions of AA by stages. In this article, three new etiology and pathogenesis have been summarized as the pathogenic Qi invades the collaterals, the stagnation of Qi and blood in the collaterals, and the deficiency of the collaterals. The treatment principle of AA is mainly refined into three stages, which include clearing heat, removing dampness, and harmonizing the collaterals for the initial stage; invigorating Qi, cultivating blood, and dredging collaterals for the middle stage; supplementing the liver, nourishing the kidney and enrich the collaterals for the terminal stage. The main ways of treatment include oral and external application of Chinese medicine and TCM external therapy. (斑秃是一种常见自身免疫性脱发。在中医辨证理论指导下, 结合络病学理论, 本文探讨斑秃各期的病因病机、临床特点及治则治法方药等。斑秃的病机可总结为盛邪袭络、气血凝络、络脉亏虚, 治疗原则以初期清热除湿和络、中期益气养血通络、末期养肝益肾补络为主, 采用中药口服、外用及中医外治手法进行治疗。)